Principal Leadership in Improving Teacher Performance in Schools - Setiawan, Usep; Drajat, Drajat; Hermawan, Agus; Yusuf, Yusuf; Andriana Gaffar, M (International Journal of Educational Research & Social Sciences, 2022)
The school principal is the leader in an educational institution unit using team work, who is entrusted by the institution to lead the school and motivate work, teach, organize, mobilize and direct, for the achievement of educational goals. This study uses a qualitative approach using descriptive methods. This study aims to describe the principal's leadership in improving teacher performance. In the learning process the teacher is seen as having an important role especially in helping students to develop their potential in cognitive, affective and psychomotor abilities, the teacher also seeks to arouse curiosity, encourage independence and accuracy of intellectual logic, and create conditions for success in learning. Teacher performance can be seen and measured based on competency specifications/criteria that must be possessed by each teacher. can be displayed through the mastery of pedagogic, professional, personality and social competencies. Considering that the leadership and work motivation of school principals on teacher performance provides a correlation, it is suggested to school institutions, that teachers can improve performance as can be seen from their responsibilities in carrying out the professional duties they carry.